An A-6 subgroup member of DREB gene family positively regulates cold stress tolerance by modulating an antioxidant defense system in transgenic potato - Saba Azeem; Faiza Munir; Alvina Gul; Rabia Amir (Scientific Reports)
Abstract Cold stress adversely influences the growth, development, geographic distribution, and yield of plants. The dehydration-responsive element binding (DREB) transcription factors are central to improving plant’s ability to endure cold stress. In this work, the expression pattern of the StDREB30 (A-6) gene was analyzed in response to cold stress in transgenic potato. We provide evidence emphasizing the significance of the StDREB30 under low-temperature stress (4°C) and investigate the potential physiological, molecular and biochemical processes involved. StDREB30 expression levels were quickly elevated upon the cold exposure. Additionally, transgenic potato plants exhibited upregulation of randomly selected downstream genes (StNAC, StDREB1, StDREB2, StSAP, StGT3, and StDHN), improved photosynthetic parameters including coefficient of photochemical quenching (qL), and maximum yield of PSII (Fv’/Fm’), better stomatal performance, increased proline accumulation, decreased malondialdehyde content, electrolyte leakage, and reduced accumulation of hydrogen peroxide, and superoxide when exposed to cold stress. Moreover, StDREB30 improved reactive oxygen scavenging capabilities by stimulating the production of antioxidants such as superoxide dismutase, peroxidase, catalase, and ascorbate peroxidase. Our results propose that StDREB30 serves as a positive regulator in promoting cold tolerance. To our knowledge, no report has been published previously on the study of the StDREB30 (A-6) gene under cold stress in transgenic potatoes.